Factors affecting turnover of call centre employees in a South African short-term insurance company - Naicker, Rajendran Burton (My University, 2016)
ABSTRACT Call centres have expanded rapidly on a global level enabling the delivery of products and services to consumers in a more efficient manner. These businesses are highly dependent on human capital that remains in constant interaction with consumers. The main challenge encountered in the call centre industry was employee turnover. High levels of employee turnover negatively impacts the business due to the cost of recruiting and training replacement employees, as well as the drop in performance standards following the loss of skilled workers. This research focuses on identifying the factors responsible for employee turnover in a single case study of a short-term insurance company. Using semi structured interviews, 12 employees were interviewed at a leading short-term insurance company in South Africa. There were many factors noted as causes of employee turnover, these included salary structure, lack of teamwork, stressful working conditions, having to deal with difficult clients, the inability to meet performance standards and opportunities arising because of new competitors entering the market. The findings obtained from management within the organisation indicated that they were generally aware of the reasons employees considered terminating their employment. As this research focused on a single case study, the findings cannot be generalised to other call centre businesses in South Africa, however, they do indicate the challenges faced by employees that contributed to them leaving the organisation.
M.B.A. Thesis
Keywords: Labor turnover, Call centers -- South Africa -- Management